Teaching Narrative Texts in Young Learners’ Classroom During Pandemic Covid-19: An Analysis from A Multiliteracies Perspective - Iffianti Azka Atsani; Ika Lestari Damayanti (Universitas Pendidikan Indonesia, 2022)
There is an urgency in education to situate literacy instruction in practices that are responsive to the globalized, multilingual world we live in. The New London Group (1996) has predicted the situation and conceptualized multiliteracies, which view literacy as supplemental, continual, and modifying established literacy teaching and learning rather than replacing traditional teaching and learning practices (Rowsell, Kosnik, Beck, 2008). With the pandemic Covid-19 outbreaks, all schools were forced to be online, encompassing the principles of more than just a traditional literacy pedagogy. Thus, this study aims to see types of teaching and learning resources and pedagogical acts conducted in the classroom seen from multiliteracies perspective during the online classroom. This qualitative study explored the teaching and learning resources and the pedagogical acts based on the multiliteracy pedagogy perspective. The data was collected from classroom observation, interview with the teacher and document analysis. The results showed that the teacher in this study mostly focused on Situated Practice and Overt Instruction in teaching narrative texts in an online classroom. This indicated that the teaching and learning practices only focused on the knowledge process of experiencing and conceptualising. The teacher did not really promote the process of analysing-both functionally and critically- and applying creatively. Keywords: Multiliteracies, Narrative texts, COVID-19, English for Young learners